Advancing emergency obstetric care in India: progress, challenges, and the road ahead - Pawalia, Kalpana; Dhiman, Anchal; Gopal, K. Madan (International Journal Of Community Medicine And Public Health, 2025)
One of the key strategies to reduce maternal and newborn mortality is to improve the availability, accessibility, and use of emergency obstetric and newborn care (EmONC) services. The emergency obstetric care (EmOC) and life-saving anesthetic skills (LSAS) training programs were initiated in the early 2000s in the country to tackle the shortage of skilled providers in critical care during childbirth in India. However, these training programs are still based on a curriculum developed around 15 years ago, which does not account for modern healthcare challenges, technological advancements, or the diverse conditions encountered in the field. A narrative review was conducted, and secondary data was analysed from the Government portal related to emergency obstetric care services in the States. Interviews were held with key stakeholders’ expertise in policy from the National level and from the program implementation at the State level. Through a detailed examination, the article elucidates the evolution of this curriculum, transformative changes introduced, the recent developments and the technical changes incorporated in the revised EmOC and LSAS curriculum drafted in 2024, highlighting the need and importance of these trainings. The article also delves into the progress with respect to the Emergency Obstetric care services in India so far, the current challenges and bottlenecks in implementing this program over the States, and provides insights and suitable recommendations for further improving the emergency obstetric care services in the country.